2002
DOI: 10.1021/ja0271274
|View full text |Cite
|
Sign up to set email alerts
|

Mononuclear Nitrogen/Sulfur-Ligated Zinc Methoxide and Hydroxide Complexes:  Investigating Ligand Effects on the Hydrolytic Stability of Zinc Alkoxide Species

Abstract: The synthesis and properties of mononuclear zinc methoxide ([(ebnpa)Zn-OCH3]ClO4) (1) and hydroxide ([(ebnpa)Zn-OH]ClO4) (2) complexes of a new mixed nitrogen/sulfur ligand (ebnpa = N-2-(ethylthio)ethyl-N,N-bis(6-neopentylamino-2-pyridylmethyl)amine) are reported. The structures of 1 and 2 were determined by X-ray diffraction. Each possesses a single zinc-coordinated anion (methoxide or hydroxide) and exhibits an overall trigonal bipyramidal geometry. Structural and spectroscopic studies indicate the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 14 publications
1
43
0
Order By: Relevance
“…An early example of 5-coordinate Zn involves the work of Teixidor et al [50] with long Zn-S contacts of 2.63-2.74 Å, whereas Garner et al [51] later reported a similar case, now with just one Zn-S bond (2.49 Å). With pyrazoles, Bouwman found distances of 2.67-2.68 Å [52], whereas Berreau reported much shorter distances of 2.29-2.43 Å [53].…”
Section: The Zn-s(thioether) Bond Lengths In Coordination Compoundsmentioning
confidence: 99%
“…An early example of 5-coordinate Zn involves the work of Teixidor et al [50] with long Zn-S contacts of 2.63-2.74 Å, whereas Garner et al [51] later reported a similar case, now with just one Zn-S bond (2.49 Å). With pyrazoles, Bouwman found distances of 2.67-2.68 Å [52], whereas Berreau reported much shorter distances of 2.29-2.43 Å [53].…”
Section: The Zn-s(thioether) Bond Lengths In Coordination Compoundsmentioning
confidence: 99%
“…Traditional syntheses of (L) n M/OH complexes involve self-assembly [25][26][27][28] or substitution [29,30] reactions with excess OH À /H 2 O in protic solvents. Here we describe a new strategy involving aprotic conditions (THF) and a nearly stoichiometric amount of water to give the hydroxide-containing complexes [(Py 2 S) 4 Fe 5 (m-OH) 2 ](BF 4 ) 4 (3) and [(Py 2 S) 2 Fe 2 (m-OH)]BF 4 (4).…”
Section: Introductionmentioning
confidence: 99%
“…[19] To examine the influence of hydrogen bonding on the formation and reactivity of nitrogen/sulfurligated zinc-aryloxide and -alkoxide complexes, two new tetradentate tripodal ligand systems containing one or more internal hydrogen-bond donors were employed ( Figure 8). [46,55] Using the bmnpa and benpa ligands, a series of mononuclear N 2 S 2 -ligated zinc-aryloxide complexes were prepared and characterized. [46] In each complex, a hydrogen-bonding interaction is present between the zinc-bound aryloxide oxygen atom and the secondary amine moiety of the supporting chelate ligand.…”
Section: Metal Hydroxide/co 2 Chemistrymentioning
confidence: 99%
“…1 Particularly interesting results were obtained using the tripodal N 3 S-donor ebnpa {[2-(ethylthio)ethyl]bis[(6-neopentylamino-2-pyridyl)methyl]amine} ligand (Figure 8). [55] The mononuclear zinc-methoxide and -hydroxide complexes, [ …”
Section: Metal Hydroxide/co 2 Chemistrymentioning
confidence: 99%